Emerging trend of Dairy based Producer Organizations :Case Studies from Himachal Pradesh - Thakur, Devesh; Sharma, Krishnender; Sharma, Manoj; Suman, Madhu (Indian Journal of Dairy Science, 2021)
The present study assessed the functioning of dairy-based producer organizations in the hills of Himachal Pradesh. Milk price fetched by farmers across various marketing channels is one of the lowest in the country. The organized milk marketing structure of the state is one of the weakest in the country. Lower remunerative returns have affected the attitude of farmers towards dairy farming. Innovative farmer organizations are making progress in the state. These organizations offer input services to farmers at lower prices at doorsteps. They also buy milk at prices higher than prevailing rates. Farmer producer organizations have emerged as new models of agribusiness in India. The reported evidence of dairy interventions through based producer organizations are still minimal from this region. The paper examines theÂ functioning of three farmer organizations in the state. These three organizations engage in community mobilizationÂ through Self-help groups. The benefits accrued by members range from financial literacy,input availability, community fodder banks, and dairy marketing.